Landbot-Based Interactive Chatbot as a Tax Learning Medium for 11th-Grade Vocational High School Students in Accounting and Financial Institutions - Mafaza, Siti Hidanati; Nanda, Hanjar Ikrima; Prinstin, Eren (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2025)
Taxation learning in vocational high schools still faces various challenges, such as difficult material, limited use of interactive media, and low student motivation. This study aims to examine the effectiveness of an interactive chatbot based on Landbot as a learning medium for Income Tax material for 11th-grade Accounting and Financial Administration students at a private SMK in Malang Regency. Using a Research and Development method at the implementation stage and a one-group pretest-posttest design, this study measured students’ understanding before and after using the chatbot through learning outcome tests. The Wilcoxon Signed-Rank test results showed a significance value of 0.000 (< 0.05), indicating a significant improvement in learning outcomes. The average student score increased from 67.41 to 91.30 after the treatment. This proves that the interactive chatbot is effective enhancing comprehension of taxation material and provides a more engaging and flexible learning experience tailored to the needs of SMK students.